Development of a novel airbag system of abdominal compression for reducing respiratory motion: preliminary results in healthy volunteers. (16th May 2022) - Li, Wenxin; Konishi, Kenta; Ohira, Keiichi; Hirata, Masanori; Wakabayashi, Kohei; Aramaki, Shuhei; Sakamoto, Masataka; Nakamura, Katsumasa
Abstract: This study used cine-magnetic resonance imaging (cine-MRI) to evaluate the safety and efficacy of a novel airbag system combined with a shell-type body fixation system in reducing respiratory motion in normal volunteers. The airbag system consists of a six-sided polygon inflatable airbag, a same shape plate, a stiff air supply tube, an air-supply pump and a digital pressure load cell monitor. Piezoelectric sensors were installed in the plate to detect compression pressure load changes; pressure load data were transferred to the digital pressure load cell monitor through Bluetooth. Five volunteers underwent cine-MRI with and without airbag compression to detect differences in the respiratory motion of the organs. The volunteers' physiologic signs were stable during the experiment. The maximum inspiration pressure load was 4.48 ± 0.86 kgf (range, 4.00–6.00 kgf), while the minimum expiration pressure load was 3.69 ± 0.95 kgf (range, 2.8–5.3 kgf). Under airbag compression, the right diaphragm movement was reduced from 19.50 ± 6.43 mm to 9.60 ± 3.61 mm ( P < 0.05) in the coronal plane and 23.12 ± 6.30 mm to 11.00 ± 3.69 mm ( P < 0.05) in the sagittal plane. The left diaphragm, pancreas and liver in the coronal plane and the right kidney and liver in the sagittal plane also showed significant movement reduction. This novel airbag abdominal compression system was found to be safe during the experiment and successful in the reduction of internal organ respiratory motion and promises to be a convenient and efficient tool for clinical radiotherapy.